INAR(2) MODEL FOR NUMBER OF CLAIMS - (NIM: 20810002); Pembimbing: Khreshna I.A. Syuhada, M.Sc, Ph.D., RAFIDHA
Number of claims made by policyholder on a portofolio in a period is very important to know because the insurance companies have to fulfill the benefit payments for claims in accordance to the insurance policy so that these number of claims need to be modeled dan predicted for the next period using INAR(2) model. In this thesis, we will discuss the PoINAR(2) and GINAR(2) model with binomial thinning operator. We find that the marginal distribution of Xt is not affected by the inovation processes t. Yule-Walker Estimation dan Conditional Maximum Likelihood Estimation is used to estimate the parameters. Finally, we predict number of claims using one-step ahead prediction and two-step ahead prediction which the latter is better than the former.